Non-linear PID control of AC current and DC voltage for a photovoltaic system operating on a microgrid - Pablo Proaño; Marcelo Pozo; Carlos Gallardo; Oscar Camacho (Results in Control and Optimization)
This study introduces a nonlinear control strategy to enhance the energy management of electrical power systems, addressing the inherent limitations of traditional linear PI controllers. The proposed approach incorporates a variable gain that dynamically adjusts based on the system error, amplifying the PI controller’s responsiveness without causing output saturation. By introducing quadratic error terms through the gain adjustment, the controller achieves nonlinear behavior. When the system error is significant, the gain increases to expedite correction; as the error approaches zero, the gain decreases, allowing the PI controller to maintain stability around the reference. This adaptive behavior eliminates the need for a derivative component, effectively circumventing challenges posed by electromagnetic noise and rapid system dynamics. A comparative analysis between the proposed nonlinear PI controller and a conventional PI controller is conducted within a photovoltaic microgrid framework. The results highlight the nonlinear controller’s superior performance in achieving robust and accurate control.